Intrusive Narratives: Mental Health and Discourse Patterns in “Turtle All The Way Down” - Virtianti, Rika; Yuliasari, Ria; Prihatna Sari, Ferdias (Universitas Nasional, 2025)
Abstract This study explores the linguistic representation of intrusive thoughts in the film Turtles All the Way Down, focusing on how language reflects the main character Aza Holmes’s experience of obsessive-compulsive disorder (OCD). The research aims to identify how repetition, interruption, and metaphor function as linguistic signs of anxiety and self-fragmentation. Using a qualitative descriptive method, selected dialogues and inner monologues from the film script were analyzed through James Paul Gee’s discourse analysis framework, which views language as a form of social action and identity construction. The findings show that repetition expresses Aza’s compulsive thought cycles, interruption reflects the intrusion of anxiety into social communication, and metaphor—particularly those involving bacteria, infection, and parasites—externalizes her fear and loss of control. These linguistic features reveal a constant tension between Aza’s inner discourse and her outward social interaction. The study concludes that Turtles All the Way Down portrays OCD not only as a psychological condition but also as a discursive experience, where language becomes both a symptom and a means of recovery. Keywords: Intrusive Narrative, Mental Health, Discourse Pattern